Antiplatelet Therapy Changes for Patients With Myocardial Infarction With Recurrent Ischemic Events: Insights Into Contemporary Practice From the TRANSLATE‐ACS (Treatment With ADP Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome) Study - Alexander C. Fanaroff; Lisa A. Kaltenbach; Eric D. Peterson; Mohammed W. Akhter; Mark B. Effron; Timothy D. Henry; Tracy Y. Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundGuidelines recommend P2Y12 inhibitor therapy for 1 year after myocardial infarction (MI), yet little guidance is provided on antiplatelet management for patients with recurrent ischemic events during that year. We describe changes in P2Y12 inhibitor type among patients with recurrent ischemic events in the first year after MI. Methods and ResultsThe TRANSLATE‐ACS (Treatment With ADP Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome) study enrolled 12 365 patients with MI treated with percutaneous coronary intervention. We examined whether P2Y12 inhibitor choice changed among patients with recurrent MI, stent thrombosis, and/or unplanned revascularization during the first year after MI, and modeled factors associated with P2Y12 inhibitor intensification (changing clopidogrel to prasugrel or ticagrelor). In the first year after MI, 1414 patients (11%) had a total of 1740 recurrent ischemic events (771 recurrent MIs, 969 unplanned revascularizations, and 165 stent thromboses). Median time to the first recurrent ischemic event was 154 days (25th–75th percentiles, 55–287 days). Of those with recurrent ischemic events, 101 of 1092 (9.3%) occurring in clopidogrel‐treated patients led to P2Y12 inhibitor intensification. Recurrent events involving stent thrombosis or MI were the strongest factors associated with P2Y12 inhibitor intensification, yet only 40% of patients with stent thrombosis and 14% of patients with recurrent MI had P2Y12 inhibitor intensification. Increasing age and longer time from the index MI were associated with lower likelihood for intensification. ConclusionsFew patients after MI with a recurrent ischemic event who were taking clopidogrel switched to a more potent P2Y12 inhibitor, even after stent thrombosis events. Specific guidance is needed for patients who have recurrent ischemic events, particularly when closely spaced. Clinical Trial RegistrationURL: https://www.clinicaltrials.gov. Unique identifier: NCT01088503.